A Content-Addressable Memory Structure using Novel Majority Gate with 5-input in Quantum-dot Cellular Automata - Majeed, Ali Hussien; Zainal, Mohd Shamian; Alkaldy, Esam; Md Nor, Danial (International Journal of Integrated Engineering, 2020)
Quantum-dot Cellular Automata (QCA) circuits are very promising in term of technology and suitable replacement for CMOS circuits. The main building blocks for this technology are majority gate and inverter. Content Addressable Memory (CAM) is commonly used in applications that require high speed memory. In this paper, a novel five input majority gate is introduced, this gate is simulated with QCADesigner tool, and compared with previous same structures. Then, the proposed gate used to design CAM cell in a single layer after derive the minority gate from proposed majority gate. The proposed CAM design has a simple and robust structure and does not require wire crossover, also it reduces the complexity of the circuit compared to the existing structures